C-Reactive Protein Levels Predict Responses to PD-1 Inhibitors in Hepatocellular Carcinoma Patients - Zhang, Yiyang; Lu, Lianghe; He, Zhangping; Xu, Zhishen; Xiang, Zhicheng; Nie, Run-Cong; Lin, Wenping; Chen, Wenxu; Zhou, Jie; Yin, Yixin; Xie, Juanjuan; Zhang, Youcheng; et al. (Frontiers in Immunology, 2022)
Background: Serum C-reactive protein (CRP) is a biomarker of an acute inflammatory response and has been successfully used as a prognostic predictor for several malignancies. However, the clinicopathological significance of CRP levels in hepatocellular carcinoma (HCC) patients being treated with PD-1 inhibitors remains unclear. Methods: Serum CRP levels were measured for a total of 101 HCC patients that had been treated with PD-1 inhibitors from July 2018 to November 2019. The clinicopathological data was retrospectively analyzed to identify any clinical implications between CRP levels and responses to PD-1 inhibitors and patients’ progression-free survival (PFS). Results: The median PFS was 8.87 months in the CRP-low subgroup and 3.67 months in the CRP-high subgroup (P = 0.009). Univariate and multivariate Cox regression analysis demonstrated that both serum CRP and AFP levels were independent risk factors for the PFS of HCC patients treated with PD-1 inhibitors (P < 0.05). Moreover, Cox regression analysis after Propensity Score Matching showed the similar results. A prognostic model combining CRP and AFP levels could significantly stratify HCC patients receiving PD-1 inhibitors into low-, intermediate-, and high-risk subgroups (P < 0.001). Patients in the risk subgroups reported similar overall response rates (P = 0.625) and significantly different disease control rates (low- vs. intermediate- vs. high-risk groups: 81.6% vs. 65.1% vs. 35%, respectively, P = 0.002). Conclusions: The results of this study support the association between high serum CRP levels with the response and PFS for HCC patients receiving PD-1 inhibitors. Furthermore, the levels of both CRP and AFP in an HCC patient before treatment initiation show great potential for determining the efficacy of PD-1 inhibitors.